Pengaruh Konsentrasi Nutrisi AB Mix terhadap Pertumbuhan dan Produksi Tiga Varietas Tomat Cherry (Solanum lycopersicum var. cerasiforme) Hidroponik Sistem NFT - Urfan, Mohamad; Wahyuni, Endang Sri (JURNAL AGROPLANT, 2025)
Hydroponics is used as a solution to the problems in conventional plant cultivation, such as soil fertility, fertilization, irrigation, pest and disease attacks, and the decreasing availability of agricultural land. This research aims to determine the best concentration of AB Mix nutrients for the growth and production of three varieties of cherry tomatoes (Solanum lycopersicum var. cerasiforme) in a hydroponic NFT system. This study used a 3 x 3 factorial Randomized Complete Design (RCD) with three replications. The first factor was the concentration of AB Mix nutrients (K), consisting of three levels: 700 ppm, 1000 ppm, 1400 ppm (K1); 900 ppm, 1200 ppm, 1700 ppm (K2); and 1100 ppm, 1400 ppm, 2000 ppm (K3). The second factor was the variety (T), which consisted of three varieties: Cherry Tomato (T1), Golden Sweet Tomato (T2), and Red Ruby Tomato (T3). Data from observations were analyzed using an F-test to determine the effects of the treatments. If significant differences were found, Duncan’s Multiple Range Test (DMRT) at the 0.05 level was applied. Data analysis was performed using SPSS 26 for Windows. The results of the study showed that the best AB Mix nutrient concentration (900–1700 ppm) promoted the best growth and production in all three cherry tomato varieties, based on plant height, number of leaves, number of fruits per plant, number of fruits per bunch, and fruit weight. The cherry tomato variety demonstrated the best growth and production. The best interaction was found between the AB Mix nutrient concentration (900–1700 ppm) and the cherry tomato variety.